PENGARUH GAYA KEPEMIMPINAN DAN IKLIM ORGANISASI TERHADAP KEPUASAN KARYAWAN DI KANTOR INSPEKTORAT KABUPATEN BADUNG - Wijaya, I Gede Artha; Wibawa, I Made Artha (E-Jurnal Manajemen; Vol 6 No 1 (2017), 2017)
Job satisfaction is a feeling that demonstrated the employee to work in an organization. If the non-fulfillment of the factors that may affect employee job satisfaction, hence causing job dissatisfaction, so it can be received various complaints from employees. The emergence of job dissatisfaction at Inspectorate Office Badung Regency because to lack of employment intentions, the lack of morale, come to work late and even to leave work early. The purpose of this study was to examine the influence of leadership style and organizational climate on employee job satisfaction. This research was conducted at Inspectorate Office Badung Regency. Total population in this study as many as 75 people and the number of respondents taken as many as 71 people. Data collection methods used in this research was conducted through interviews and questionnaires. The analysis technique used in this research is multiple linear regression analysis. The results showed that the leadership style and organizational climate positive and significant impact on job satisfaction.
Keywords: leadership style, organizational climate, job satisfaction